Energy-saving intensification of gas-condensate field production in the East of Ukraine using foaming reagents - Shendrik, O.; Fyk, M. I.; Biletskyi, V. S.; Kryvulia, S.; Donskyi, D.; Alajmeen, A.; Pokhylko, A. (Dnipro University of Technology, 2019)
Purpose. Development of recommendations on the use of foaming surfactants (FSs) in the overall task of increasing energy and resource conservation of wells at the final stages of the development of gas condensate fields (GCFs). Methods. To achieve the goal and solve the set tasks, following methods were used: active experiment method, regression and correlation analyzes of the obtained statistical data, comparative analysis of technological regulations for the intensification of well production. Findings. Recommendations on the use of the studied FSs for intensifying the extraction of gas-condensate fluids with the specification of the geological and field characteristics of exploited fields in Eastern Ukraine in terms of Shebelynske and Zakhidno-Khrestyshchenske GСF were developed. Originality. The dependence of the cross-correlation coefficient of the "additional gas production with the use of FSs – the number of well stimulation operations" upon the period of the influence of the FSs on the reservoir – well system, being of extreme nature, has been determined. It has been established that the effectiveness of the use of the additional part of productions debit depends linearly on the initial production rate and exponentially on the frequency of the well FS-treatment. Practical implications. It has been determined that the maximum manifestation of the impact of considered FSs on downhole fluid production is achieved after 2 months. Various techniques for the application of the FSs were tested, and the regulations for the corresponding field operations were specified. Optimization of the parameter charts and processing procedures in terms of the concentration of FSs, system connection of the foam injection pipeline to the well, the rational period of introduction of the FSs in the reservoir-well system results in the decrease of the total downtime of wells during the period of operation under conditions of intensification as well as methane pollutions during purges.

Мета. Розробка рекомендацій щодо використання піноутворючих поверхнево-активних речовин (ПАР) в загальному завданні збільшення енерго- та ресурсозбереження обводнених свердловин на завершальних стадіях розробки газоконденсатних родовищ. Методика. Для досягнення мети і вирішення поставлених завдань використовувалися наступні методи досліджень: метод активного експерименту, регресійний і кореляційний аналізи отриманих статистичних даних, компаративний аналіз технологічних регламентів інтенсифікації свердловинного видобутку. Результати. Розроблено рекомендації щодо використання досліджених ПАР для інтенсифікації видобутку газоконденсатних флюїдів з уточненням геолого-промислових характеристик експлуатованих родовищ Сходу України на прикладі Шебелинського та Західно-Хрестищенського газоконденсатних родовищ. Наукова новизна. Визначено залежність коефіцієнта взаємної кореляції кривих "додатковий видобуток газу при застосуванні ПАР – кількість свердловин-операцій інтенсифікації від періоду впливу ПАР на систему "пласт – свердловина", яка носить екстремальний характер. Встановлено, що ефективність застосування ПАР лінійно залежить від початкового дебіту та експоненціально від частоти обробки свердловини. Практична значимість. Встановлено, що максимальні прояви впливу розглянутих ПАР на свердловинний видобуток флюїдів досягається через два місяці. Випробувані різні методики застосування ПАР, уточнені регламенти відповідних промислових робіт. Оптимізація режимних карт і регламентів обробок у частині концентрації ПАР, схемного підключення інгібіторопровода піноутворення до свердловини, раціонального періоду введення ПАР в систему "пласт – свердловина" призводить до зменшення сумарного часу простоїв свердловин за період експлуатації в умовах інтенсифікації, а також викидів метану в атмосферу при продувках.
Енергозберігаюча інтенсифікація видобутку газоконденсатного родовища на Сході України з використанням піноутворюючих реагентів
Keywords: resource saving; gas condensate field; geological field conditions; well flow rate; foaming surfactants; foam surface-active substances; ресурсозбереження; геолого-промислові умови; дебіт свердловини; спінююча речовина; піноутворючі поверхнево-активні речовини